Strategi Pengembangan Bank Syariah dengan Menggunakan Analisis SWOT (Studi Kasus di Kabupaten Toba) - Sugianto Sugianto; Muhammad Arif; Muhammad Irfan (Jurnal Ilmiah Ekonomi Islam, 2022)
Islamic syaria teaches the procedure of muamalah in several forms of contracts, one of which is the musharaka contract. The practice of Muamalah-Musyarakah contracts was used in the Islamic financial prosperity is very advanced but Islamic banking does not exist, even though there are many government-owned banks that have long been established. The purpose of this study was to determine the development strategy, opportunities and challenges of establishing a sharia bank in Toba Regency . The research approach used in this study is a descriptive qualitative approach, with a SWOT analysis method. The results of this study indicate that the strategy of developing Islamic banks in the autonomous region of Toba Regency increases the promotion and socialization of Islamic bank products. The opportunity to establish a sharia bank in the autonomous region of Toba Regency, has a large enough opportunity as evidenced by the Banking Law & MUI Fatwa, the MUI fatwa on usury shows that the Banking Law and MUI Fatwa can influence and encourage prospective customers to trust funds in Islamic banks. The challenges of establishing a sharia bank in the autonomous region of Toba Regency, namely the conventional system and other financial institutions that are more developed, make it a challenge for the development of sharia banks in Toba Regency, as well as the lack of promotion or socialization of Islamic financial institutions in Toba Regency, because the community has never been in direct contact with the bank Syariah.